Unravelling the synergistic interaction of Thrips tabaci and newly recorded, Thrips parvispinus with Alternaria porri (Ellis.) Cif., inciting onion purple blotch - Saini, Shubham; Raj, Kushal; Saini, Anil Kumar; Kumar, Rakesh; Saini, Ankit; Khan, Aslam; Kumar, Pankaj; Devi, Geeta; Bhambhu, Mukul Kumar; McKenzie, Cindy L.; Lal, Makhan; Wati, Leela (Frontiers in Microbiology, 2024)
Onion purple blotch is the most indispensable foliar disease of crop and has become a major concern for farmers and research fraternity. An attempt to investigate the role of injury in parasitism by Alternaria porri indicated that disease incidence and severity enhance considerably with injury. Thrips injured plants inoculated with A. porri presented 100 per cent incidence and 52-72 per cent severity while mechanically injured plants inoculated with A. porri showed 60-70 per cent incidence and 28-34 per cent severity. The uninjured plants showed considerably less disease incidence (30-40 per cent) and severity (10-16 per cent). Injured inoculated plants presented reduced leaf length and leaf area while the leaf diameter remained unaffected. The lesion number, lesion length and size was substantially enhanced with concomitant infestation of pest and pathogen. Thrips tabaci injury led to more pronounced symptoms of purple blotch compared to Thrips parvispinus injury. There was substantial decrease in photosynthetic rate and chlorophyll content with stress imposed on plant whilst the relative stress injury was enhanced. The induction of injury and inoculation of A. porri had an impact on the concentration of total phenolics, total soluble sugars, total proteins and hydrogen peroxide in onion leaves. A. porri combined with injury caused a more pronounced decrease in total soluble sugars and total protein content while enhancement in total phenolics and hydrogen peroxide content compared to uninjured plants. The dynamic nature of morpho-physiological and biochemical changes owing to stress conditions imposed on onion plant adds an extra layer of complexity in understanding the onion plant physiology and their ability to work out in response to challenging environment conditions.